Impact of STN-DBS on life and health satisfaction in patients with Parkinson's disease. Issue 3 (1st September 2009) - Ferrara, Joseph; Diamond, Alan; Hunter, Christine; Davidson, Anthony; Almaguer, Michael; Jankovic, Joseph
Abstract : Objective: Advanced Parkinson's disease (PD) is associated with various motor and non-motor symptoms which adversely impact health-related quality of life (HRQoL). Subthalamic nucleus (STN) deep brain stimulation (DBS) has been reported to improve some dimensions of HRQoL in appropriately selected candidates. Prior studies of HRQoL following DBS have used instruments comprising a predetermined list of questions which assess issues that are generally relevant in PD, but that may not be of equal or consistent importance to all individuals. In this study, we evaluate the effect of STN DBS on quality of life using the QLS M, a modular questionnaire in which satisfaction scores for each item are weighted in light of patient-rated importance. Methods: We prospectively analysed QLS M scores in 21 patients with PD (11 men, mean age 61.5±8.6 years) before STN DBS surgery and at a mean 7.4±1.5, and again at a mean 16.6±6.8 months postoperatively. Results: Following STN DBS, patients experienced an improvement in HRQoL as measured by various items of the movement disorder and health modules of the QLS M . Specifically, QLS M items pertaining to energy level/enjoyment of life, independence from help, controllability/fluidity of movement and steadiness when standing and walking showed significant improvements, although items concerning general life issues (eg, occupational function, interpersonal relationships, leisure activities) did not improve. Conclusion: Following STN DBS, symptomatic and functional improvements translate into higher HRQoL, with high satisfaction in domains related to movement disorders and general health.